Control of electric machine drive system - Sul, Seung-Ki. (Hoboken, N.J. : Wiley-IEEE, 2011)
'This book is based on the author's industry experience. It contains many exercise problems that engineers would experience in their day-to-day work'--
Includes bibliographical references.
Keywords: Electric driving -- Automatic control